Factors associated with knowledge, attitude and practice in sexual and reproductive health among Malaysian postgraduate students at Universiti Putra Malaysia - Soleymani, Shahla (2014)
Sexual health issues faced by young people are premarital sexual intercourse, sexually transmitted diseases, unwanted pregnancies, unsafe abortions and human immunodeficiency virus infection. Knowledge about sexual and reproductive health is very important for young people to prevent behaviors that place them at risk of contracting sexually transmitted diseases and unwanted pregnancy. The aim of this study was to determine the knowledge, attitude and practice related to sexual and reproductive health among Malaysian postgraduate students in Universiti Putra Malaysia. A cross-sectional study design was used. The study population was Malaysian postgraduate students in Universiti Putra Malaysia, using systematic random sampling. Data was collected from 5th of September to 28th of September 2012 using a pre-tested self-administrated questionnaire. Data was analyzed using SPSS version 20.0. The significant level was set at p < 0.05. Response rate was 100%. Out of the 434 Malaysian postgraduate students, 21.4% were male and 78.6% were female. Majority were Malays (70.3%) followed by Chinese (18.2%) and Indians (8.1%). The overall mean age of respondents was 26.95 years (95% CI 26.54-27.36) and ranged from 20 years to 46 years. The mean age of the males and females were 26.82 (±SD 4.125) year and 27.41 (±SD 4.91) years, respectively. The main sources of information for sexual and reproductive health awareness reported by the respondents were the internet (78.6%) and newspaper (61.8%). The overall mean knowledge score of students on sexual and reproductive health was 30.27 (SD ±8.58) and ranged from 0 to 69 points. The result of this study revealed that the majority (97.9%) of students knew that AIDS is a sexually transmitted disease. Almost 81.3% of students knew about syphilis, 24.4% about chlamydia and 37.09% about gonorrhea respectively. More than half of the participants believed that the spread of sexually transmitted diseases was through casual contact, such as using public toilet (77.4%), through kissing (64.5%) and through shaking hands (92.1%). The students’ answers regarding the ways of avoiding sexually transmitted diseases were abstaining from sexual intercourse (20.7%), having one uninfected faithful sex partner (85.57%) and using condom (88.4%) during sexual activity. Mean attitude score toward sexual and reproductive health was 20.02 (SD ±9.91) and ranged from 0 to 46 points. Mean practice score regarding sexual and reproductive health was 4.14 (SD ±4.50) and ranged from 0 to 22 points. The results also showed that marital status (F =14.94, p = 0.001) and faculty (F =21.21, p = 0.001) were the associated factors with knowledge of sexual and reproductive health. Attitude related to sexual and reproductive health was significantly associated with marital status (F = 12.67, p = 0.001). The practice of respondents related to sexual and reproductive health was significantly associated with gender (F = 191.93, p = 0.001) and ethnicity (F = 8.75, p = 0.003). In conclusion, the result of study showed that the knowledge related to sexual and reproductive health among Malaysian postgraduate students in Universiti Putra Malaysia is not satisfactory. The respondents seem to have unfavorable attitude on the prevention of sexually transmitted diseases. Usage of condom is low among those who had sexual intercourse. Intervention programs related to sexual and reproductive health are recommended to improve the knowledge, attitudes and practice of Malaysian postgraduate students.